PENGARUH IKLAN TELEVISI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SABUN LUX (SURVEI PADA PENGUNJUNG MEGA BEKASI HYPERMALL) - Wibowo, Setyo Ferry; Karimah, Maya Puspita (Fakultas Ekonomi, Universitas Negeri Jakarta, 2012)
Generaly, the purpose of this research are: 1) To determine the analytical description of the television advertisement, price and purchase decision of Lux soap (Survey on visitors of Mega Bekasi Hypermall), 2) To determine the effect of television advertisement on purchase decision of Lux soap, 3) To determine the effect of price on purchase decision of Lux soap, 4) To determine the effect of the television advertisement, price and purchase decision of Lux soap (Survey on Visitors of Mega Bekasi Hypermall). The analysis which has been applied in this study is multiple linear regression analysis. The study has been conducted with a convinence sampling technique of 110 consumers who visited Mega Bekasi Hypermall, while the technique of data collection was done by distributing questionnaires which were processed by SPSS 19. According to the research that the t test result on the variable of television advertisement is 2,965 with a significant value of 0.004,which means that the television advertisement has a significant influence on purchase decision. Furthermore, the t test result on the price variable is 3,678 with significant value of 0.000, which means that the price has a significant effect on purchase decision. Whereas, the F test result of two variables television advertisement and price is 9,087 with a significance value of 0,000. Those figures descibes that the television advertisement and price simultaneously have significant influence on a purchase decision. In addition, the F test R2 value that is resulted from the research is 0.145 or 14.5%. This value describes the television advertisement and price influence on purchase decision as 14.5%. Keywords: Television Advertisement, Price, Purchase Decision.